Synthetic Biology and iGEM: Techniques, Development and Safety Concerns An Omics Big-data Mining Perspective - Ning, Kang.; Zhan, Yi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on biological engineering techniques, multi-omics big-data integration, and data-mining techniques, as well as cutting-edge researches in principles and applications of several synthetic biology applications. Synthetic biology is a new research area, while it has been rooted from the long-established area including biological engineering, metabolite engineering, and systems biology. This book will discuss the following aspects: (1) introduction to synthetic biology and iGEM, especially focusing on the systematic design, rational engineering, and sustainability of design in the omics ages; (2) synthetic biology-related multi-omics data integration and data mining techniques; (3) the technical issues, development issues, and safety issues of synthetic biology; (4) data resources, web services, and visualizations for synthetic biology; and (5) advancement in concrete research on synthetic biology, with several case studies shown. Devised as a book on synthetic biology research and education in the omics age, this book has put focuses on systematic design, rational engineering, and sustainability of design for synthetic biology, which will explain in detail and with supportive examples the "What," "Why," and "How" of the topic. It is an attempt to bridge the gap between synthetic biology's research and education side, for best practice of synthetic biology and in-depth insights for the related questions.
Chapter 1. Introduction to Synthetic Biology -- Chapter 2. iGEM: The Competition on Synthetic Biology -- Chapter 3. Synthetic Biology-related Multi-omics Data Integration and Data Mining Techniques -- Chapter 4. Synthetic Biology: Technical Issues -- Chapter 5. Synthetic Biology: Development Issues -- Chapter 6. Synthetic Biology: Safety Issues -- Chapter 7. Synthetic Biology: Data Resources, Web Services and Visualizations -- Chapter 8. Synthetic Biology: Case Studies -- Chapter 9. Concluding Remarks.
Keywords: Bioinformatics; Biotechnology; Data mining; Bioinformatics; Biotechnology; Data Mining and Knowledge Discovery